Indoor Air Quality of a Medical Faculty Hospital and Its Effect on Those in the Environment - Güllü Eren; Lütfi Saltuk Demir (Genel Tıp Dergisi)

(untitled)
Background: Indoor air quality is associated with the etiopathogenesis of many diseases. This condition also produces many medical symptoms. The purpose of the current study is to measure indoor air quality parameters in a medical faculty hospital and to determine the medical complaints of hospital staff and patients/patient relatives related to the indoor air quality.Methods: This cross-sectional, descriptive research was conducted with 442 participants between February 28 and March 22, 2021. For the indoor air quality in the hospital; temperature, relative humidity, air flow rate, light level, nitrogen oxide (NO), hydrogen sulfide (H2S), sulfur dioxide (SO2), carbon monoxide (CO), carbon dioxide (CO2) gas levels were evaluated according to the standards. The association between socio-demographic characteristics, medical complaints and indoor air quality were analyzed in hospital staff and patients/patient relatives.Results: It was determined that 80.3% of the air temperature and 22.7% of the relative humidity measurements in the study were in the standard limits and almost all of the air flow velocity and 81.0% of the illumination level measurements were not in standard limits. It was determined that particulate matter level was measured normal levels according to International Organization for Standardization (ISO) 5 class in the all-environmental area. NO, H2S and SO2 were detected in the hospital with indoor gas measurements. CO gas was detected in a small part of the hospital. The majority of CO2 measurements were in line with standards. The most common symptoms of the participants associated with indoor air of the hospital were fatigue, dyspnea, and dysesthesia.Conclusion: While most of the hospital indoor temperature measurements were in accordance with the standards, most of the humidity, airflow velocity and lighting measurements were not in accordance with the standards. NO, H2S, SO2 gases were not detected in the hospital, while CO was detected in 2 areas.